du | 1 | du | |||||||||||||
jeśli ∫ | = − | ∫ | : | ||||||||||||
−2u + 3 | 2 |
|
du | 1 | dt | 1 | |||||
∫ | = − | ∫ | = − | ln|−2u + 3| | ||||
−2u + 3 | 2 | t | 2 |
1 | ||
− | = du | |
2 |
1 | du | 1 | dt | 1 | 3 | ||||||||||||||||
− | ∫ | = − | ∫ | = − | ln|u − | | | |||||||||||||||
2 |
| 2 | t | 2 | 2 |
3 | ||
t = u − | ||
2 |
1 | 3 | 1 | ||||
− | ln|u − | | = − | ln|−2u + 3| to równanie prawdziwe? | |||
2 | 2 | 2 |
1 | 3 | |||
wynik − | ln|u − | | + C był podany przez profesora na wykładzie, co jest więc nie | ||
2 | 2 |
1 | 1 | 3 | ||||
− | ln|−2u + 3| + C = − | ln|−2 * (u − | )| + C = | |||
2 | 2 | 2 |
1 | 1 | 3 | 1 | 3 | ||||||
− | ln |2| − | ln|u − | | + C = − | ln|u − | | + C1 | |||||
2 | 2 | 2 | 2 | 2 |
du | ||
∫ | = ∫dx | |
−2u + 3 |
3 | ||
u = | + Ce−2x | |
2 |